2010
DOI: 10.4067/s0717-97072010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interactions Between Copper(ii) Acetate Monohydrate and Orotic Acid and Orotate Ligands

Abstract: Different complexes by reacting copper(II) acetate monohydrate with orotic acid and orotate as ligands were prepared. These compounds were characterized by elemental analysis, spectroscopy, and thermal analysis. It is suggested that in both compounds, the Cu 2 (acetate) 4 suffers the break of both acetate groups by a substitution of orotic or orotate ligands, increasing the Cu-Cu distance. It was corroborated by the magnetic moment values of 1.65 and 1.82 B.M for these compounds.The anion orotato(-1) coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The molar proportion of acetate decreased when adding 60 µg Cu/g DM or more (Table ), probably because the precipitation of acetate as copper acetate, Cu 2 (CH 3 COO), decreased the detection of acetate in the medium . Zhang et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The molar proportion of acetate decreased when adding 60 µg Cu/g DM or more (Table ), probably because the precipitation of acetate as copper acetate, Cu 2 (CH 3 COO), decreased the detection of acetate in the medium . Zhang et al .…”
Section: Resultsmentioning
confidence: 98%
“…23 The molar proportion of acetate decreased when adding 60 μg Cu/g DM or more (Table 1), probably because the precipitation of acetate as copper acetate, Cu 2 (CH 3 COO), decreased the detection of acetate in the medium. 26 Zhang et al 25 reported a reduction in acetate when adding 10-20 μg Cu/g DM without affecting the concentrations of propionate and butyrate; likewise, this might be because most of the acetate had been converted to CH 4 . 10 However, in the present study, supplying above of 60 μg Cu/g DM caused a decrease in the molar proportion of acetate and CH 4 production.…”
Section: Resultsmentioning
confidence: 98%
“…The optimization and frequency calculation of both the Cu(II) complexes and Co(II) complexes were performed using both semi-empirical method (PM3) and DFT (B3LYP/6-31G*) DFT levels of calculations based on the preliminary stability study. Semi-emperical method (PM3) was considered along with DFT since PM3 have been successfully used either alone or with other theoretical methods for structural analysis of Cu(II) complexes [15][16][17][18][19][20] . Density functional theory (DFT) calculations were performed with the hybrid B3LYP exchange and correlation functional 21,22 and 6-31G(d) basis set.…”
mentioning
confidence: 99%